MsmR1, a global transcription factor, regulates polymyxin synthesis and carbohydrate metabolism in Paenibacillus polymyxa SC2 - Zhao, Dongying; Li, Hui; Cui, Yanru; Tang, Shengyue; Wang, Chengqiang; Du, Binghai; Ding, Yanqin (Frontiers in Microbiology, 2022)
The transcription factor multiple-sugar metabolism regulator (MsmR), belonging to the AraC/XylS family, participates in polysaccharide metabolism and virulence. However, the transcriptional regulatory mechanisms of MsmR1 in Paenibacillus polymyxa remain unclear. In this study, knocking out msmR1 was found to reduce polymyxin synthesis by the SC2-M1 strain. Chromatin immunoprecipitation assay with sequencing (ChIP-Seq) revealed that most enriched pathway was that of carbohydrate metabolism. Additionally, electromobility shift assays (EMSA) confirmed the direct interaction between MsmR1 and the promoter regions of oppC3, sucA, sdr3, pepF, yycN, PPSC2_23180, pppL, and ydfp. MsmR1 stimulates polymyxin biosynthesis by directly binding to the promoter regions of oppC3 and sdr3, while also directly regulating sucA and influencing the citrate cycle (TCA cycle). In addition, MsmR1 directly activates pepF and was beneficial for spore and biofilm formation. These results indicated that MsmR1 could regulate carbohydrate and amino acid metabolism, and indirectly affect biological processes such as polymyxin synthesis, biofilm formation, and motility. Moreover, MsmR1 could be autoregulated. Hence, this study expand the current knowledge of MsmR1 and will be beneficial for the application of P. polymyxa SC2 in the biological control against the certain pathogens in pepper.